(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article analyzes the theory and practice of protecting wheat varieties from biotic stress factors. Protection of wheat from pests, diseases, and viruses is a significant issue in agriculture. The article examines the main biotic stresses affecting wheat and their impact on yield, as well as modern technologies and methods for managing them. Approaches such as molecular selection, CRISPR/Cas9 technology, biological control and Integrated Pest Management (IPM) are presented as effective tools for protecting wheat from biotic factors. This article will be useful for agronomists, breeders, and agricultural specialists.